Using Microtechnology to Quantify Torso Angle During Match-Play in Field Hockey. Issue 10 (October 2019) - Warman, Geoffrey E.; Cole, Michael H.; Johnston, Rich D.; Chalkley, Daniel; Pepping, Gert-Jan
Abstract : Abstract: Warman, GE, Cole, MH, Johnston, RD, Chalkley, D, and Pepping, GJ. Using microtechnology to quantify torso angle during match-play in field hockey. J Strength Cond Res 33(10): 2648–2654, 2019—Field hockey is played in a dynamic environment placing specific postural demands on athletes. Little research has been devoted to understanding the nature of a player's torso postures in field hockey match-play and its relationship with the perceptuomotor demands of the sport. We used commercially available microtechnology worn by 16 athletes during a 6-match national tournament to quantify torso flexion/extension angles. Orientation was derived using the inertial and magnetic sensors housed within global positioning system devices, assessing torso angle in the sagittal plane from 91 individual match files. The main independent variable was playing position, whereas the dependent variable was torso flexion/extension, presented as a percentage of playing time spent in 15 × 10° torso postural bands ranging from ≥40° extension to ≥90° flexion. It was shown that athletes spent 89.26% of their playing time in various torso postures, ranging from 20 to 90° of flexion. Defenders spent more time than midfielders ( p = 0.004, effect size [ES] = 0.43) and strikers ( p = 0.004; ES = 0.44) in the posture band of 10–20° torso flexion, whereas midfielders spent more time between 20 and 30° of torso flexion ( p = 0.05; ES = 0.32) than strikers. Conversely, strikers spent more time between 30 and 40° of flexion than defenders ( p < 0.001; ES = 0.74). These results reflect the sport-specific and role-specific torso angles adopted by field hockey athletes during match-play. Coaching staff can use these data to gain insight into the postural demands of their sport and inform the preparation of athletes for the perception-action demands of competition.